Healthy Wetlands, Healthy People: Educating and Mobilizing Youths for Reducing Water Pollution and Sedimentation in Lakes of Pokhara Valley, Nepal - Kafle, Mohan (Journal of Wetlands Ecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> No abstract. Journal of Wetlands Ecology Vol.1(1/2) 2008, p.14